Folic acid in pregnancy and mortality from cancer and cardiovascular disease: further follow-up of the Aberdeen folic acid supplementation trial. Issue 8 (8th April 2015) - Taylor, Caroline M; Atkinson, Charlotte; Penfold, Chris; Bhattacharya, Sohinee; Campbell, Doris; Davey Smith, George; Leary, Sam; Ness, Andy
Abstract : Background: Supplemental periconceptional folic acid is recommended to reduce the risk of fetal neural tube defects. A previous report indicated an elevated risk of breast cancer and all cancer deaths in later life among women randomised by alternate allocation to high-dose (5 mg/day) folic acid in pregnancy compared with placebo; however, findings were based on small numbers of cases. Our aim was to extend the previous analysis by including data from an additional 10 years of follow-up. Methods: Records of participants in a large (n=2928) trial of folate supplementation (5 or 0.2 mg folic acid, or placebo) in pregnancy in the 1960s were linked to central registries in Scotland. Unadjusted and adjusted HRs were calculated for all-cause, cardiovascular, all cancer and breast cancer mortality, and all cancer and breast cancer morbidity. Analyses were done using (1) data from the time of the previous linkage (2002) to March 2013; and (2) data from 1980 to March 2013. Results: There was no evidence to suggest an excess risk of morbidity or mortality in either supplementation group compared with placebo for 2002–2013 and no associations were seen for the full time period (1980–2013). Conclusions: Findings from this extended follow-up do not support our previous observation of an elevated risk of mortality from breast cancer or all cancers in later life among women who had taken 5 mg folic acid/day during pregnancy. Furthermore, there were no associations with risk of mortality from all-causes, all cancers or cardiovascular disease.